Social Identity Formation As a Trigger for Criminal Behavior in Youth Motorcycle Gangs: A Case Study in an Urban Area - Bambang Mudjiyanto; Fit Yanuar; Launa Launa (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore empirical data related to the phenomenon of crime and the process of social identity formation of motorcycle gangs in urban areas. This study is qualitative with a constructivist paradigm and socio-psychological and socio-cultural approaches. This study found several facts, namely that the phenomenon of motorcycle gangs—whose members are mostly teenagers—has long experienced a shift in orientation and behavior, the impact of the influence of the internal and external social environment. This shift resulted in a number of symbolic constructions: motorcycle gangs are criminal entities. The study also found theoretical difficulties in identifying the positive self-concept of adolescents in motorcycle gang entities whose orientation and behavior have been acutely contaminated by the culture and symbols of intolerant, antisocial, psychotic, bipolar, and obsessive compulsive disorder group identities.